Analysis of Client Importance and Workload in Predicting Fraud Behavior in Local Government - Fitria Fertha Agustina; Andi Mulyono (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study examines the relationship between client importance and workload in predicting fraudulent behavior by emphasizing the role of client frequency and reputation, work time and volume, productivity level, auditor knowledge, and doubtful attitudes. Located in a local government, the study highlights how these constructs influence fraudulent behavior. Using a questionnaire and analyzed with multiple linear regression, this study shows that client importance and workload can predict fraudulent behavior. Clients who frequently interact and communicate with auditors motivate auditors to be more thorough and meticulous in conducting audits. However, this effect will not occur if auditors have limited working hours with a large volume of work, resulting in decreased audit productivity and potentially leading to accounting irregularities. This finding also provides the view that when auditors are easily convinced and believe what others say, fraud will be easier to commit, so auditors must have a doubtful attitude towards clients.